2009
DOI: 10.1016/j.bbapap.2008.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant protein misfolding and aggregation on bacterial membranes

Abstract: The expression of recombinant proteins is known to induce a metabolic rearrangement in the host cell. We used aggregation-sensitive model systems to study the effects elicited in Escherichia coli cells by the aggregation of recombinant glutathione-S-transferase and its fusion with the green fluorescent protein that, according to the expression conditions, accumulate intracellularly as soluble protein, or soluble and insoluble aggregates. We show that the folding state of the recombinant protein and the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…S6C), suggesting that the decrease in nitrocefin hydrolysis activity in the ⌬rsaF a F b strain is likely caused by internal RsaA accumulation. This result is consistent with recent findings that internal protein accumulation and aggregation can trigger decreased membrane permeability, altered membrane composition, and lipid arrangement in E. coli (56)(57)(58). Hence, RsaF a and RsaF b likely did not play a major role in providing outer membrane integrity to protect against toxicity of antimicrobials.…”
Section: Fig 2 Spotting On Pye Plates Shows That After 2 Days Of Incusupporting
confidence: 81%
“…S6C), suggesting that the decrease in nitrocefin hydrolysis activity in the ⌬rsaF a F b strain is likely caused by internal RsaA accumulation. This result is consistent with recent findings that internal protein accumulation and aggregation can trigger decreased membrane permeability, altered membrane composition, and lipid arrangement in E. coli (56)(57)(58). Hence, RsaF a and RsaF b likely did not play a major role in providing outer membrane integrity to protect against toxicity of antimicrobials.…”
Section: Fig 2 Spotting On Pye Plates Shows That After 2 Days Of Incusupporting
confidence: 81%
“…A recent study provides the first experimental evidence that aggregation of recombinant cytoplasmic proteins affects directly the lipid moiety of bacterial membranes (Ami et al, 2009). It was shown that protein aggregation and misfolding induce changes, such as carbonylation or oxidation of host-specific proteins, a reduction in membrane permeability and rearrangements of its lipid components.…”
Section: Toxicity Of Aggregatesmentioning
confidence: 99%
“…In this way, it is possible to study lipid phase transitions and changes in lipid composition (Casal & Mantsch, 1984). For instance, through the analysis of the changes in the CH2 and CH3 absorption bands, the stress response induced by protein aggregation in bacterial cells has been monitored in situ (Ami et al, 2009). Furthermore, through the CH stretching region analysis of mouse oocyte FTIR spectra and supported by the ester carbonyl band around 1740 cm -1 (see below), Wood and colleagues (Wood et al, 2008) found that lipids -whose composition within the oocytes drastically changes during maturation stages -could be considered potential markers of oocyte developmental competence.…”
Section: Ftir Spectroscopy Of Biomolecules: Proteins Nucleic Acids mentioning
confidence: 99%